2020
DOI: 10.1007/s00705-020-04609-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel cytorhabdovirus with a unique genomic organization infecting yerba mate (Ilex paraguariensis) in Argentina

Abstract: The genome of a novel rhabdovirus was detected in yerba mate (Ilex paraguariensis St. Hil.). The newly identified virus, tentatively named yerba mate virus A (YmVA), has a genome of 14,961 nucleotides.Notably, eight open reading frames were identified in the antigenomic orientation of the negative-sense, single-stranded viral RNA, including two novel accessory genes, in the order 3'-N-P-3-4-M-G-L-8-5'. Sequence identity of the encoded proteins as well as phylogenetic analysis suggest that YmVA is a new member … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…In the last few years, several novel plant rhabdoviruses, which may be asymptomatic, have been reported in HTS studies [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Thus, it is tempting to speculate that some plant rhabdovirus-like sequences may be hidden in published plant transcriptome databases, generated with diverse objectives beyond virus research, where viral RNA was inadvertently copurified with endogenous plant RNA and sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, several novel plant rhabdoviruses, which may be asymptomatic, have been reported in HTS studies [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Thus, it is tempting to speculate that some plant rhabdovirus-like sequences may be hidden in published plant transcriptome databases, generated with diverse objectives beyond virus research, where viral RNA was inadvertently copurified with endogenous plant RNA and sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 39 apple trees tested, 11 were found positive, 2 in Agia and 9 in Zagora, implying that it is most probably a plant infecting virus. The genome organization was similar to that of rhabdoviruses with some interesting characteristics: the genome seemed to lack the glycoprotein encoding gene, as has been recently described for citrus associated cytorhabdovirus by and encodes for an accessory protein between the L and 5'-trailer, similarly to the genome of yerba mate cytorhabdovirus A (Bejerman et al, 2020). Phylogenetic analysis showed that the new virus grouped within cytorhabdoviruses (Figure 4.13).…”
Section: Discussionsupporting
confidence: 52%
“…All other predicted proteins had no significant matches with any GenBank deposited sequences. So far, the existence of a gene between L gene and 5'-trailer has only been reported in yerba mate cytorhabdovirus A (Bejerman et al, 2020). Typical for all plant rhabdoviruses, intergenic 'gene junction' conserved regions between ORFs were also identified in ZAGORA_15 sequence (Figure 4.12).…”
Section: Putative Novel Cytorhabdovirusmentioning
confidence: 97%
“…In the last few years, several novel cytorhabdoviruses which do not induce visible disease symptoms have been reported in HTS studies (Bejerman et al, 2020; Belete et al, 2023; Bolus et al, 2021; Kauffmann et al, 2022; Kopke et al, 2023; Lee et al, 2022; Liu et al, 2021; Medberry et al, 2022; Petrzik et al, 2022; Safarova et al, 2022; Wu et al, 2023). Moreover, many novel cytorhabdoviruses were identified when metatranscriptomic data publicly available at the Transcriptome Shotgun Assembly (TSA) sequence databases was mined (Bejerman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ten betacytorhabdoviruses had two ORFs between the P and M genes, while three others had four ORFs between these genes (Dietzgen et al, 2020). One of these ORFs encodes the putative cell-to-cell movement protein, which is named as P3 in all but the Yerba mate virus A, where this protein is named P4 (Bejerman et al, 2020). The other accessory proteins are named P4, P5 and P6.…”
Section: Discussionmentioning
confidence: 99%